Egypt : Beyond Stabilization. Toward a Dynamic Market Economy - Handy, Howard (Washington, D.C. : International Monetary Fund, 1998)
Determined macroeconomic policy, combined with favorable external developments, has reduced inflation, improved public finances, led to a stable currency, and helped strengthen the banking system in Egypt. Nonetheless, the task of delivering sustained growth of output and employment is incomplete. This paper is a collection of studies focusing on economic developments in Egypt in the 1990s, a period of transformation toward a dynamic market economy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet